تجلِّيات التَّناص في ديوان "سماء أخرى" للشاعرة الأديبة " شيرين عدوي - إسماعيل, علي محمود الأصمعي (International Conference on Islamic Studies, 2021)
Poetry is a language in its finest form, as Robert Crawford said, and it is the product of all the creators of the world, such as the brightness of the soul and conscience, the power of meditation, the beauty of photography in all the intellectual and moral currents of our age, and Egyptian poetry, the product of a living document, and a reference that indicates itself, its cases are derived from the life of society. And written by the creative soul, Here lies the peculiarity with which the Arab poet, Dr. Sherine Adawy wove her book “Another Heaven” because the word is a pulse bridge on that. The Holy Qur’an and its stories, and invoked some poems of modern Arab poetry, as well as some ancient myths, such as the legend of “Venus” and Eris, in order to color her poetic experience. Manifestations, Intertextuality, Another Sky, Shirin Adew